Intellective and nonintellective determinants of achievement in Mathematics among FEU engineering freshmen - Torres, Cesar Flores. 4 0 16; 5
u
Thesis (Ph.D.) -- Pamantasan ng Lungsod ng Maynila, 1986.;A dissertation presented to the faculty of Graduate School of Arts, Sciences and Education in partial fulfillment of the requirements for the degree Doctor of Education major in Educational Administration.
Keywords: 2 -- 0; 6; 20; 20; 2